Development of Ubiquitin Tools for Studies of Complex Ubiquitin Processing Protein Machines - Sui, Xin; Li, Yi-Ming (Current Organic Chemistry, 2019)
Ubiquitination is one of the most extensive post-translational modifications in eukaryotes and is involved in various physiological processes such as protein degradation, autophagy, protein interaction, and protein localization. The ubiquitin (Ub)-related protein machines include Ub-activating enzymes (E1s), Ub-conjugating enzymes (E2s), Ub ligases (E3s), deubiquitinating enzymes (DUBs), p97, and the proteasomes. In recent years, the role of DUBs has been extensively studied and relatively well understood. On the other hand, the functional mechanisms of the other more complex ubiquitin-processing protein machines (e.g., E3, p97, and proteasomes) are still to be sufficiently well explored due to their intricate nature. One of the hurdles facing the studies of these complex protein machines is the challenge of developing tailor-designed structurally defined model substrates, which unfortunately cannot be directly obtained using recombinant technology. Consequently, the acquisition and synthesis of the ubiquitin tool molecules are essential for the elucidation of the functions and structures of the complex ubiquitin-processing protein machines. This paper aims to highlight recent studies on these protein machines based on the synthetic ubiquitin tool molecules.
Keywords: proteasome